Polyimide high-temperature dielectric composite film and preparation method thereof

By introducing tetrafluoroethylene-perfluoropropylvinyl ether copolymer and fluorinated polyimide into the polyimide film, and using ultrasonic and heat treatment processes, a polyimide high-temperature dielectric composite film with excellent dielectric properties and high-temperature energy storage performance was prepared, solving the problem of degradation in existing films in high-temperature environments.

CN120137227APending Publication Date: 2025-06-13DONGHUA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510316664.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The existing polyimide film has deteriorated dielectric properties and poor energy storage density in high-temperature environments, which limits its application in the field of high-temperature dielectric energy storage.

Method used

By introducing tetrafluoroethylene-perfluoropropyl vinyl ether copolymer, fluorinated polyimide and polyimide to prepare a polyimide high-temperature dielectric composite film, ultrasonic treatment and heat treatment are used to form a film with high energy gap and high carrier traps.

Benefits of technology

The dielectric performance and energy storage performance of the polyimide high-temperature dielectric composite film are significantly improved, the leakage current is reduced, the breakdown strength is improved, and the film with excellent energy storage density is prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137227A_ABST
    Figure CN120137227A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer dielectric materials, in particular to a polyimide high-temperature dielectric composite film and a preparation method thereof. The preparation method comprises the following steps: mixing a fluorinated polyamic acid solution, a polyamic acid solution and a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution, performing stirring treatment and ultrasonic treatment, then coating the upper surface of a substrate with the mixed solution subjected to ultrasonic treatment, and performing drying treatment to form an initial composite film; the preparation method comprises the following steps: preparing an initial composite film, carrying out heat treatment on the initial composite film to obtain a heat-treated composite film, and finally stripping the heat-treated composite film from a substrate to obtain the polyimide high-temperature dielectric composite film with excellent dielectric properties and excellent energy storage performance in a high-temperature environment. The preparation method is simple in process and high in applicability, provides important technical support for developing high-performance and high-stability high-temperature dielectric films, and is suitable for wide popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer dielectric materials, and in particular to a polyimide high-temperature dielectric composite film and a preparation method thereof. Background Art

[0002] As a key functional material, dielectric films are widely used in high-tech fields such as aerospace, power electronics, and energy storage. However, traditional dielectric films have poor thermal stability and their dielectric properties drop sharply in high-temperature environments, limiting their applications. Therefore, the development of high-temperature dielectric films has become particularly important.

[0003] Polyimide (PI) is an aromatic heterocyclic polymer compound containing an imide ring in the main chain. Due to its excellent thermal stability and mechanical properties, it is considered to be one of the important candidate materials for high-temperature dielectric films. However, traditional polyimide films not only have a low dielectric constant, but also have poor energy storage density under high temperature environments, which greatly limits their application in the field of high-temperature dielectric energy storage.

[0004] At present, the prior art generally adopts the method of inorganic phase doping modification to improve the dielectric constant of polyimide film to improve its dielectric properties. For example, the Chinese patent technology with publication number CN 104046023 A discloses a method for preparing a high dielectric polyimide / barium titanate composite film, which introduces barium titanate to prepare a polyimide / barium titanate composite film with a high dielectric constant. Although the patent improves the dielectric constant, due to the obvious difference in dielectric properties between barium titanate and polyimide, it is easy to produce local electric field distortion in the polyimide / barium titanate composite film, resulting in an increase in its leakage current and a decrease in breakdown strength, thereby reducing the energy storage performance of the polyimide / barium titanate composite film under high temperature environment (such as a decrease in energy storage density, etc.).

[0005] Therefore, how to obtain a polyimide film having excellent dielectric properties and excellent energy storage performance under high temperature environment is a technical problem to be solved urgently in this field. Summary of the invention

[0006] The present invention provides a method for preparing a polyimide high-temperature dielectric composite film. The polyimide high-temperature dielectric composite film having excellent dielectric properties and excellent energy storage performance under a high-temperature environment can be prepared by the preparation method.

[0007] The present invention also provides a polyimide high-temperature dielectric composite film, which is prepared by the above-mentioned preparation method. Therefore, the polyimide high-temperature dielectric composite film has excellent dielectric properties and excellent energy storage performance in a high-temperature environment.

[0008] The first aspect of the present invention provides a method for preparing a polyimide high-temperature dielectric composite film, comprising the following steps:

[0009] Mix a fluorinated polyamic acid solution and a polyamic acid solution to obtain a mixed solution, and then mix the mixed solution with a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution, followed by stirring treatment and ultrasonic treatment to obtain an ultrasonically treated mixed solution;

[0010] Coat the ultrasonically treated mixed solution on the upper surface of a substrate and then perform a drying treatment to form an initial composite film;

[0011] Place the initial composite film in a heating device and perform a heat treatment according to a set temperature program to obtain a heat-treated composite film. Then, peel the heat-treated composite film from the substrate to obtain the polyimide high-temperature dielectric composite film containing fluorinated polyimide, polyimide, and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer.

[0012] In the method for preparing a polyimide high-temperature dielectric composite film as described above, in the ultrasonically treated mixed solution, the mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is 10% - 30%.

[0013] In the method for preparing a polyimide high-temperature dielectric composite film as described above, the solid content of the fluorinated polyamic acid solution is 10% - 30%, and the solid content of the polyamic acid solution is 15% - 40%.

[0014] In the method for preparing a polyimide high-temperature dielectric composite film as described above, the mass ratio of the fluorinated polyamic acid solution to the polyamic acid solution is (0.18 - 0.54):2.5.

[0015] In the method for preparing a polyimide high-temperature dielectric composite film as described above, the set temperature program is as follows: in the first stage, heat at 80°C - 120°C for 10 min - 20 min; in the second stage, heat at 180°C - 220°C for 25 min - 40 min; in the third stage, heat at 230°C - 270°C for 25 min - 40 min; in the fourth stage, heat at 280°C - 320°C for 60 min - 240 min.

[0016] In the method for preparing a polyimide high-temperature dielectric composite film as described above, the temperature of the drying treatment is 65°C - 100°C and the time is 6 h - 24 h.

[0017] In the method for preparing a polyimide high-temperature dielectric composite film as described above, the rotation speed of the stirring treatment is 300 r / min - 1200 r / min and the time is 2 h - 8 h;

[0018] and / or, the coating rate is 50 s -1 to 200 s -1 .

[0019] The second aspect of the present invention provides a polyimide high-temperature dielectric composite film, which is prepared by the preparation method of the polyimide high-temperature dielectric composite film described above.

[0020] For the polyimide high-temperature dielectric composite film described above, in the polyimide high-temperature dielectric composite film, the highest occupied molecular orbital - HOMO energy level of the polyimide is -5.85 eV, the lowest unoccupied molecular orbital - LUMO energy level is -3.12 eV, and the energy band gap value is 2.73 eV.

[0021] For the polyimide high-temperature dielectric composite film described above, in the polyimide high-temperature dielectric composite film, the highest occupied molecular orbital - HOMO energy level of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is -9.86 eV, the lowest unoccupied molecular orbital - LUMO energy level is -0.14 eV, and the energy band gap value is 9.72 eV.

[0022] The preparation method of the polyimide high-temperature dielectric composite film provided by the present invention prepares a polyimide high-temperature dielectric composite film by introducing a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer, a fluorinated polyimide and a polyimide. In this polyimide high-temperature dielectric composite film, the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer has a high energy gap (the energy band gap value is 9.72 eV), which can inhibit the growth of electrical treeing. And a high carrier trap is formed at the interface between the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer and the polyimide (the electron trap energy level is 2.98 eV), which is beneficial to reducing the leakage current and improving the breakdown strength. Therefore, this polyimide high-temperature dielectric composite film has excellent dielectric properties and excellent energy storage properties in a high-temperature environment. Compared with the traditional method, the preparation method provided by the present invention significantly reduces the leakage current and improves the breakdown strength, and can prepare a polyimide high-temperature dielectric composite film with excellent energy storage density. The preparation method of the present invention has simple process and strong applicability, provides important technical support for the development of high-performance and high-stability high-temperature dielectric films, and is suitable for wide promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0024] Figure 1 This is the scanning electron microscope (SEM) test result diagram of the polyimide (PI) high-temperature dielectric composite film in Example 4 of the present invention; among them, Figure 1 (a) of is the SEM plan view of the polyimide (PI) high-temperature dielectric composite film at 500 nm, Figure 1 (b) of is the SEM cross-sectional view of the polyimide (PI) high-temperature dielectric composite film at 5 μm, Figure 1 (c) of is the SEM cross-sectional view of the polyimide (PI) high-temperature dielectric composite film at 500 nm, Figure 1 (d) of is the SEM cross-sectional view of the polyimide (PI) high-temperature dielectric composite film at 200 nm;

[0025] Figure 2 This is the energy dispersive spectroscopy (EDS) test result diagram of the polyimide (PI) high-temperature dielectric composite film in Example 4 of the present invention; among them, Figure 2 (a) of is the distribution diagram of C element in the polyimide (PI) high-temperature dielectric composite film, Figure 2 (b) of is the distribution diagram of N element in the polyimide (PI) high-temperature dielectric composite film, Figure 2 (c) of is the distribution diagram of O element in the polyimide (PI) high-temperature dielectric composite film, Figure 2 (d) of is the distribution diagram of F element in the polyimide (PI) high-temperature dielectric composite film. Detailed implementation manners

[0026] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are some, rather than all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0027] The raw materials and reagents used in the following embodiments can be obtained from commercial channels without special instructions; the processes used, without special instructions, are all conventional processes in the art.

[0028] The first aspect of the present invention provides a method for preparing a polyimide high-temperature dielectric composite film, including the following steps:

[0029] Mix the fluorinated polyamic acid solution and the polyamic acid solution to obtain a mixed solution, and then mix the mixed solution with a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution and perform stirring treatment and ultrasonic treatment to obtain the ultrasonically treated mixed solution;

[0030] After coating the ultrasonic-treated mixed solution on the upper surface of the substrate, a drying treatment is carried out to form an initial composite film;

[0031] The initial composite film is placed in a heating device and then heat-treated according to a set temperature program to obtain a heat-treated composite film. Then, after peeling the heat-treated composite film from the substrate, a polyimide high-temperature dielectric composite film containing fluorinated polyimide, polyimide, and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is obtained.

[0032] The present invention does not particularly limit the sources or specific preparation methods of the fluorinated polyamic acid solution, polyamic acid solution, and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution. They can be obtained through commercial channels or prepared by methods well-known in the art.

[0033] The present invention does not particularly limit the specific equipment of the heating device, which can be selected according to actual needs. In some embodiments, the initial composite film can be placed in a muffle furnace and then heat-treated according to a set temperature program.

[0034] The present invention does not particularly limit the frequency, power, and time of the ultrasonic treatment, which can be selected according to actual needs. The present invention also does not particularly limit the specific equipment for ultrasonic treatment, and ultrasonic equipment well-known to those skilled in the art can be used for ultrasonic treatment.

[0035] The present invention does not particularly limit the specific operation method of coating, which can be carried out according to methods known to those skilled in the art. In some embodiments, the ultrasonic-treated mixed solution can be coated on the surface of the substrate by a doctor blade method.

[0036] The object of the present invention for preparation is a polyimide high-temperature dielectric composite film. Specifically, in the present invention, a fluorinated polyamic acid solution and a polyamic acid solution are mixed to obtain a mixed solution, and then the mixed solution is mixed with a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution and then subjected to stirring treatment and ultrasonic treatment to obtain a mixed solution after ultrasonic treatment. The stirring treatment is to make the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution and the mixed solution fully mixed and uniform, and the ultrasonic treatment is to remove the bubbles in the solution after the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution and the mixed solution are mixed; the mixed solution after ultrasonic treatment is coated on the surface of a substrate and then dried to remove the solvent to form an initial composite film; the initial composite film is placed in a heating device and then heat-treated according to a set temperature program to cause the polyamic acid and fluorinated polyamic acid in the initial composite film to undergo thermal imidization reactions respectively, dehydrating and cyclizing into polyimide and fluorinated polyimide to obtain a composite film after heat treatment; then the composite film after heat treatment is peeled off from the substrate to obtain a polyimide high-temperature dielectric composite film containing fluorinated polyimide, polyimide and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer. In this polyimide high-temperature dielectric composite film, the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer has a high energy gap (the energy band gap value is 9.72 eV), which can effectively inhibit the growth of electrical trees and improve the breakdown strength, and a high carrier trap is formed at the interface between the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer and polyimide (the deep electron trap energy level is 2.98 eV), which is beneficial to reducing the leakage current and improving the energy storage density. Therefore, this polyimide high-temperature dielectric composite film has excellent dielectric properties and excellent energy storage properties in a high-temperature environment.

[0037] In a specific embodiment, in the above-mentioned mixed solution after ultrasonic treatment, the mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is 10% to 30%.

[0038] When the mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer in the above-mentioned mixed solution after ultrasonic treatment is within the above range, a polyimide high-temperature dielectric composite film with excellent dielectric properties and excellent energy storage properties in a high-temperature environment can be prepared.

[0039] Exemplarily, in the mixed solution after ultrasonic treatment, the mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer can be any one of 10%, 15%, 20%, 25%, 30% or a range composed of any two of them.

[0040] In a specific embodiment, the solid content of the above-mentioned fluorinated polyamic acid solution is 10% to 30%, and the solid content of the above-mentioned polyamic acid solution is 15% to 40%; the mass ratio of the fluorinated polyamic acid solution to the polyamic acid solution is (0.18 to 0.54):2.5.

[0041] When the parameters of the solid content of the fluorinated polyamic acid solution, the solid content of the polyamic acid solution, and the mass ratio of the fluorinated polyamic acid solution to the polyamic acid solution are each within the above ranges, the mixed solution obtained by mixing the fluorinated polyamic acid solution and the polyamic acid solution can be liquid-phase compatible with the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution and form a uniform solution, which is beneficial to the subsequent preparation of a polyimide high-temperature dielectric composite film with excellent dielectric properties and excellent energy storage properties in a high-temperature environment.

[0042] In a specific embodiment, the above-mentioned set temperature program is as follows: the first stage is heated at 80 °C to 120 °C for 10 min to 20 min, the second stage is heated at 180 °C to 220 °C for 25 min to 40 min, the third stage is heated at 230 °C to 270 °C for 25 min to 40 min, and the fourth stage is heated at 280 °C to 320 °C for 60 min to 240 min.

[0043] When heat treatment is carried out according to the above-mentioned set temperature program, the polyamic acid and fluorinated polyamic acid in the initial composite film can respectively undergo thermal imidization reactions, dehydrating and cyclizing into polyimide and fluorinated polyimide, which is beneficial to obtaining a polyimide high-temperature dielectric composite film containing fluorinated polyimide, polyimide and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer, and this polyimide high-temperature dielectric composite film has excellent dielectric properties and excellent energy storage properties in a high-temperature environment.

[0044] In a specific embodiment, the temperature of the above-mentioned drying treatment is 65 °C to 100 °C and the time is 6 h to 24 h.

[0045] When the parameters of the temperature and time of the above-mentioned drying treatment are each within the above ranges, the solvent in the mixed solution after ultrasonic treatment can be effectively formed into an initial composite film, which is beneficial to the subsequent preparation of a polyimide high-temperature dielectric composite film with excellent dielectric properties and excellent energy storage properties in a high-temperature environment.

[0046] In a specific embodiment, the rotation speed of the above-mentioned stirring treatment is 300 r / min to 1200 r / min and the time is 2 h to 8 h.

[0047] When the parameters of the rotation speed and time of the stirring treatment are each within the above ranges, the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution and the above-mentioned mixed solution can be fully mixed and homogenized.

[0048] In a specific embodiment, the coating rate is 50 s -1 ~200 s -1 .

[0049] When the coating rate is within the above range, the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer in the mixed solution after ultrasonic treatment can form an oriented structure in the initial composite film through the shearing force during the doctor blade coating process, which is beneficial to inhibiting the growth of electrical tree branches, forming high carrier traps at the interface between the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer and polyimide, reducing the leakage current and improving the breakdown strength, thereby preparing a polyimide high-temperature dielectric composite film with excellent dielectric properties and excellent energy storage properties under high-temperature environments.

[0050] The second aspect of the present invention provides a polyimide high-temperature dielectric composite film prepared by the preparation method of the above polyimide high-temperature dielectric composite film.

[0051] Specifically, in the present invention, after mixing a fluorinated polyamic acid solution, a polyamic acid solution, and a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution, stirring treatment and ultrasonic treatment are carried out to obtain a mixed solution after ultrasonic treatment. Then, the mixed solution after ultrasonic treatment is coated on the surface of a substrate and dried to form an initial composite film. Next, the initial composite film is placed in a heating device and heat-treated according to a set temperature program to obtain a heat-treated composite film. Finally, after peeling the heat-treated composite film from the substrate, a polyimide high-temperature dielectric composite film containing fluorinated polyimide, polyimide, and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is obtained. The polyimide high-temperature dielectric composite film has excellent dielectric properties and excellent energy storage properties under high-temperature environments.

[0052] In a specific embodiment, in the above polyimide high-temperature dielectric composite film, the highest occupied molecular orbital - HOMO energy level of polyimide is -5.85 eV, the lowest unoccupied molecular orbital - LUMO energy level is -3.12 eV, and the band gap value is 2.73 eV.

[0053] When the parameters of the highest occupied molecular orbital - HOMO energy level, the lowest unoccupied molecular orbital - LUMO energy level, and the band gap value of polyimide in the polyimide high-temperature dielectric composite film are the above values, it is beneficial to form high carrier traps at the interface between polyimide and the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer, thereby reducing the leakage current and increasing the energy storage density.

[0054] In a specific embodiment, in the above polyimide high-temperature dielectric composite film, the highest occupied molecular orbital - HOMO energy level of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is -9.86 eV, the lowest unoccupied molecular orbital - LUMO energy level is -0.14 eV, and the band gap value is 9.72 eV.

[0055] When the parameters of the highest occupied molecular orbital (HOMO) energy level, the lowest unoccupied molecular orbital (LUMO) energy level, and the energy band gap value of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer in the polyimide high-temperature dielectric composite film are within the above ranges, the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer has a wide energy band gap, which can effectively inhibit the growth of electrical treeing and improve the breakdown strength of the composite film; it is beneficial to form high carrier traps at the interface between the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer and polyimide, reduce the leakage current and increase the energy storage density.

[0056] Hereinafter, the present invention will be further introduced through specific embodiments.

[0057] Example 1

[0058] The preparation method of the polyimide high-temperature dielectric composite film provided in this example includes the following steps:

[0059] S1. After 2,2'-bis(trifluoromethyl)benzidine and 4,4'-hexafluoroisopropyl phthalic anhydride are fully dissolved in N,N-dimethylacetamide, they are reacted in a low-temperature bath at a reaction temperature of 0 °C for 18 h to obtain a 0.18 g fluorinated polyamic acid (FPAA) solution with a solid content of 20%; after 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are fully dissolved in N,N-dimethylacetamide, they are reacted at a reaction temperature of 20 °C for 18 h to obtain a 2.5 g polyamic acid (PAA) solution with a solid content of 18%.

[0060] Mix 0.18 g of the fluorinated polyamic acid (FPAA) solution with a solid content of 20% and 2.5 g of the polyamic acid (PAA) solution with a solid content of 18% and stir for 4 h to obtain a mixed solution.

[0061] S2. Mix the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) with thinners to obtain a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) solution; mix the P(TFE-PPVE) solution with the mixed solution in S1 and stir at a rotation speed of 1000 r / min for 6 h, and then perform ultrasonic treatment to remove bubbles to obtain a mixed solution after ultrasonic treatment; the mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the mixed solution after ultrasonic treatment is 10%.

[0062] S3. Use the doctor blade method to uniformly coat the mixed solution after ultrasonic treatment in S2 on the surface of a glass substrate at a doctor blade rate of 100 s -1 and then perform drying treatment at 95 °C for 12 h to remove the solvent to form an initial composite film.

[0063] S4. Place the initial composite film in S3 in a muffle furnace and perform heat treatment according to a set temperature program to obtain a heat-treated composite film. The set temperature program is as follows: in the first stage, heat at 100 °C for 10 min, in the second stage, heat at 200 °C for 30 min, in the third stage, heat at 250 °C for 30 min, and in the fourth stage, heat at 300 °C for 120 min.

[0064] S5. After peeling the heat-treated composite film in S4 from the glass substrate, a polyimide (PI) high-temperature dielectric composite film containing fluorinated polyimide (FPI), polyimide (PI), and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) is obtained.

[0065] Example 2

[0066] The preparation method of the polyimide high-temperature dielectric composite film provided in this example is basically the same as that in Example 1, except that:

[0067] S2. The mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the mixed solution after ultrasonic treatment is 15%.

[0068] Example 3

[0069] The preparation method of the polyimide high-temperature dielectric composite film provided in this example is basically the same as that in Example 1, except that:

[0070] S2. The mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the mixed solution after ultrasonic treatment is 20%.

[0071] Example 4

[0072] The preparation method of the polyimide high-temperature dielectric composite film provided in this example is basically the same as that in Example 1, except that:

[0073] S2. The mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the mixed solution after ultrasonic treatment is 25%.

[0074] Example 5

[0075] The preparation method of the polyimide high-temperature dielectric composite film provided in this example is basically the same as that in Example 1, except that:

[0076] S2. The mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the mixed solution after ultrasonic treatment is 30%.

[0077] Comparative Example 1 (without adding tetrafluoroethylene-perfluoropropyl vinyl ether copolymer)

[0078] The preparation method of the polyimide high-temperature dielectric composite film provided in this comparative example includes the following steps:

[0079] S1. After 2,2'-bis(trifluoromethyl)benzidine and 4,4'-hexafluoroisopropyl phthalic anhydride are fully dissolved in N,N-dimethylacetamide, they are reacted in a low-temperature bath at a reaction temperature of 0 °C for 18 h to obtain a 0.18 g fluorinated polyamic acid (FPAA) solution with a solid content of 20%; after 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are fully dissolved in N,N-dimethylacetamide, they are reacted at a reaction temperature of 20 °C for 18 h to obtain a 2.5 g polyamic acid (PAA) solution with a solid content of 18%.

[0080] Mix 0.18 g of the fluorinated polyamic acid (FPAA) solution with a solid content of 20% and 2.5 g of the polyamic acid (PAA) solution with a solid content of 18% and stir for 4 h to obtain a mixed solution.

[0081] S2. Use the doctor blade method to uniformly coat the mixed solution in S1 on the surface of a glass substrate at a doctor blade rate of 100 s -1 and then perform a drying treatment at 95 °C for 12 h to remove the solvent, forming an initial composite film.

[0082] S3. Place the initial composite film in S2 in a muffle furnace and perform heat treatment according to a set temperature program to obtain a heat-treated composite film; the set temperature program is as follows: the first stage is heated at 100 °C for 10 min, the second stage is heated at 200 °C for 30 min, the third stage is heated at 250 °C for 30 min, and the fourth stage is heated at 300 °C for 120 min.

[0083] S4. After peeling the heat-treated composite film in S3 from the glass substrate, a polyimide high-temperature dielectric composite film containing fluorinated polyimide (FPI) and polyimide (PI) is obtained.

[0084] Comparative Example 2 (without adding fluorinated polyamic acid)

[0085] The preparation method of the polyimide high-temperature dielectric composite film provided in this comparative example includes the following steps:

[0086] S1. After 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are fully dissolved in N,N-dimethylacetamide, they are reacted at a reaction temperature of 20 °C for 18 h to obtain a 2.5 g polyamic acid (PAA) solution with a solid content of 18%.

[0087] S2. Mix tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) with thinner to obtain a solution of tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)); mix the P(TFE-PPVE) solution with the PAA solution in S1 and stir at a rotation speed of 1000 r / min for 6 h, then perform ultrasonic treatment to remove bubbles to obtain a mixed solution after ultrasonic treatment; the mass fraction of tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the mixed solution after ultrasonic treatment is 10%.

[0088] S3. Use the doctor blade method to uniformly coat the mixed solution after ultrasonic treatment in S2 on the surface of a glass substrate at a doctor blade rate of 100 s -1 and then perform drying treatment at 95 °C for 12 h to remove the solvent, forming an initial composite film.

[0089] S4. Place the initial composite film in S3 in a muffle furnace and perform heat treatment according to a set temperature program to obtain a composite film after heat treatment; the set temperature program is as follows: the first stage is heated at 100 °C for 10 min, the second stage is heated at 200 °C for 30 min, the third stage is heated at 250 °C for 30 min, and the fourth stage is heated at 300 °C for 120 min.

[0090] S5. After peeling the composite film after heat treatment in S4 from the glass substrate, a polyimide high-temperature dielectric composite film containing polyimide (PI) and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) is obtained.

[0091] Comparative Example 3 (without adding tetrafluoroethylene-perfluoropropyl vinyl ether copolymer and fluorinated polyamic acid)

[0092] The preparation method of the polyimide high-temperature dielectric film provided in this comparative example includes the following steps:

[0093] S1. After 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are fully dissolved in N,N-dimethylacetamide, react at a reaction temperature of 20 °C for 18 h to obtain a 2.5 g polyamic acid (PAA) solution with a solid content of 18%.

[0094] S2. Use the doctor blade method to uniformly coat the polyamic acid (PAA) solution in S1 on the surface of a glass substrate at a doctor blade rate of 100 s -1 and then perform drying treatment at 95 °C for 12 h to remove the solvent, forming an initial composite film.

[0095] S3. Place the initial composite film in S2 in a muffle furnace and perform heat treatment according to a set temperature program to obtain a heat-treated composite film. The set temperature program is as follows: in the first stage, heat at 100 °C for 10 min, in the second stage, heat at 200 °C for 30 min, in the third stage, heat at 250 °C for 30 min, and in the fourth stage, heat at 300 °C for 120 min.

[0096] S4. After peeling the heat-treated composite film in S3 from the glass substrate, a polyimide high-temperature dielectric film is obtained.

[0097] Performance testing

[0098] 1. Based on the density functional theory (DFT), the polyimide (PI) and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) in the polyimide high-temperature dielectric composite film in Example 4 of the present invention are respectively calculated using Gaussian software. The calculation results are shown in Table 1.

[0099] (1) Highest occupied molecular orbital - HOMO energy level (E HOMO ): All calculations are performed using the hybrid B3LYP method with the 6-311G(d,p) basis set.

[0100] (2) Lowest unoccupied molecular orbital - LUMO energy level (E LUMO ): All calculations are performed using the hybrid B3LYP method with the 6-311G(d,p) basis set.

[0101] (3) Energy band gap value (E g ): E g = E LUMO - E HOMO ;

[0102] (4) Electron trap energy level (Trap): Taking the lowest unoccupied molecular orbital - LUMO energy level value as the electron affinity (E A ) of the corresponding molecular structure, the difference between the electron affinities of PI and P(TFE-PPVE) is the electron trap energy level (Trap).

[0103] Table 1 Calculation results

[0104]

[0105]

[0106] The bandgap is a key factor determining the energy storage performance of dielectric materials. In dielectric materials, the bandgap affects their ability to withstand high electric fields without breakdown. Generally, a wider bandgap corresponds to better insulation performance, making the material less likely to undergo electrical breakdown, which is crucial for high-performance capacitors and other energy storage devices. In this invention, Gaussian software based on density functional theory (DFT) was used to calculate the lowest unoccupied molecular orbital - LUMO energy level (E LUMO ), the highest occupied molecular orbital - HOMO energy level (E HOMO ), and the bandgap value (E g ) of polyimide (PI) and P(TFE-PPVE). PI is a donor-acceptor type polymer synthesized by the condensation reaction of dianhydride and diamine monomers. E g is defined as the energy difference between E LUMO and E HOMO , and its magnitude is mainly affected by the electron-donating ability of diamine and the electron-accepting ability of dianhydride. As shown in Table 1, the electron cloud density of PI is positively charged in most regions of the main chain, while the C=O group on the imide ring is negatively charged, and its calculated E g value is 2.73 eV.

[0107] As shown in Table 1, the electron cloud density of P(TFE-PPVE) is mainly negatively charged, which is mainly attributed to the large number of electron-withdrawing F atoms on the main chain of P(TFE-PPVE). The calculated E g value of P(TFE-PPVE) is 9.27 eV, which is 3.4 times that of PI; the wider bandgap endows P(TFE-PPVE) with better electrical insulation performance and lower leakage current, especially more advantageous under high-temperature conditions. Moreover, the wider bandgap helps to inhibit the growth of electrical treeing, inhibit the migration of charge carriers, reduce conductive losses, and improve the breakdown strength of the composite film.

[0108] In addition, the E A values of PI and P(TFE-PPVE) are 3.12 eV and 0.14 eV respectively, and the corresponding difference in electron trap energy levels (Trap) is 2.98 eV, indicating that a high carrier trap (electron trap energy level is 2.98 eV) is formed at the interface between PI and P(TFE-PPVE) in the polyimide high-temperature dielectric composite film. This high carrier trap is beneficial for reducing leakage current and enhancing the energy storage density.

[0109] 2. The surface morphology of the polyimide (PI) high-temperature dielectric composite film in Example 4 of the present invention was tested, and the test results are as shown in Figure 1 , where Figure 1 (a) is the SEM plan view of the polyimide (PI) high-temperature dielectric composite film at 500 nm, Figure 1(b) is the SEM cross-sectional view of the polyimide (PI) high-temperature dielectric composite film at 5 μm, Figure 1 (c) is the SEM cross-sectional view of the polyimide (PI) high-temperature dielectric composite film at 500 nm, Figure 1 (d) is the SEM cross-sectional view of the polyimide (PI) high-temperature dielectric composite film at 200 nm; the scanning electron microscopy energy spectrum test (EDS) was carried out on the polyimide (PI) high-temperature dielectric composite film in Example 4 of the present invention, and the test results are as Figure 2 shown, among which, Figure 2 (a) is the distribution map of C element in the polyimide (PI) high-temperature dielectric composite film, Figure 2 (b) is the distribution map of N element in the polyimide (PI) high-temperature dielectric composite film, Figure 2 (c) is the distribution map of O element in the polyimide (PI) high-temperature dielectric composite film, Figure 2 (d) is the distribution map of F element in the polyimide (PI) high-temperature dielectric composite film.

[0110] From Figure 1 (a)-(d), it can be seen that the cross-sectional SEM of the polyimide (PI) high-temperature dielectric composite film in Example 4 of the present invention does not show obvious spherical P(TFE-PPVE) particles, indicating that its compatibility is significantly improved. The inventor analyzed this and believed that this significant improvement in compatibility was mainly attributed to the following two points (see Figure 1 (b)): First, FPI contains more fluorine atoms, and its main chain structure is similar to the imide ring and benzene ring skeleton of PI, enabling it to interpenetrate and distribute between the PI phase and the P(TFE-PPVE) phase, effectively enhancing the compatibility between the two; second, the high viscosity of the PI / FPI / P(TFE-PPVE) blend solution (i.e., the mixed solution after ultrasonic treatment) generates a large shear stress during the doctor blade coating process, which helps the orientation and arrangement of P(TFE-PPVE) molecules, thereby further improving the compatibility.

[0111] From Figure 2 (a)-(d), it can be seen that C element, N element, O element and F element are evenly distributed in the polyimide (PI) high-temperature dielectric composite film.

[0112] 3. The following tests were carried out on the polyimide high-temperature dielectric composite films prepared in Examples 1 to 5, Comparative Examples 1 to 2, and the polyimide high-temperature dielectric film prepared in Comparative Example 3, and the test results are shown in Tables 2 and 3;

[0113] (1) Dielectric constant / 1 kHz: First, use a magnetron sputtering instrument to deposit gold electrodes on both sides of the thin film. The diameter of the gold electrodes is 6 mm, and the thickness on both sides of the film is 30 nm. Then, use a broadband dielectric impedance spectrometer (Concept 40) from a German company to conduct dielectric property tests; frequency conversion test: The test frequency range is 20 Hz to 10 6 Hz;

[0114] (2) Dielectric loss / 1 kHz: The test conditions are the same as those for the dielectric constant test;

[0115] (3) Conductivity × 10 -10 / 1 kHz (S / m): The test conditions are the same as those for the dielectric constant test;

[0116] (4) Breakdown strength (MV / m): The breakdown strength test is carried out through a high-voltage power amplifier (Trek 30 / 20A) with a voltage ramp of 500 V / s. All samples are tested more than 12 times, and the breakdown strength of the thin film samples is calculated by the Weibull statistical method;

[0117] (5) Energy storage density (J / cm 3 ): First, use a magnetron sputtering instrument to deposit gold electrodes on both sides of the thin film. The diameter of the gold electrodes is 6 mm, and the thickness on both sides of the film is 30 nm; Use the ferroelectric polarization circuit and dielectric breakdown test system of PolyK Company in the United States to obtain the dielectric displacement - electric field (D - E) curve and fatigue test results; Integrate the D - E curve with respect to the Y - axis of the coordinate axis to obtain the required energy storage density and charge - discharge efficiency;

[0118] (6) Charge - discharge efficiency (%): The test conditions are the same as those for the energy storage density test.

[0119] Table 2 Test results

[0120]

[0121]

[0122] Table 3 Test results

[0123] Item Comparative Example 1 Comparative Example 2 Comparative Example 3 Dielectric Constant / 1 kHz 3.18 3.27 3.26 Dielectric Loss / 1 kHz 0.00794 0.00875 0.00812 <![CDATA[Conductivity at 20 °C × 10 -10 / 1 kHz (S / m)]]> 5.74 5.98 6.28 Breakdown Strength at 20 °C (MV / m) 420 435 400 <![CDATA[Maximum energy storage density at 20 °C (J / cm 3 )]]> 2.31 2.38 2.041 <![CDATA[Charge and discharge efficiency at 20℃ > 90%, energy storage density (J / cm 3 )]]> 1.6 1.58 1.602 Breakdown Strength at 150 °C (MV / m) 310 325 302 <![CDATA[Maximum energy storage density at 150℃ (J / cm 3 )]]> 0.796 1.065 0.755 <![CDATA[The charge-discharge efficiency at 150°C > 90%, and the energy storage density (J / cm 3 )]]> 0.430 0.435 0.428 Breakdown Strength at 200 °C (MV / m) 265 280 248 <![CDATA[Maximum energy storage density at 200 °C (J / cm 3 )]]> 0.627 0.91 0.573 <![CDATA[Charge-discharge efficiency > 90% at 200°C, energy storage density (J / cm 3 )]]> 0.125 0.177 0.108

[0124] As can be seen from Table 2 and Table 3, compared with the polyimide high-temperature dielectric composite film in Comparative Example 1, with the increase of the content of P(TFE-PPVE), the dielectric constant of the polyimide high-temperature dielectric composite films in Examples 1 to 4 of the present invention gradually increases, and the dielectric loss significantly decreases, indicating that the addition of P(TFE-PPVE) can significantly increase the dielectric constant of the polyimide high-temperature dielectric composite film and reduce the dielectric loss. In addition, with the increase of the content of P(TFE-PPVE), the conductivity of the polyimide high-temperature dielectric composite films in Examples 1 to 4 of the present invention gradually decreases; at 20 °C, 150 °C and 200 °C, the breakdown strength, the maximum energy storage density and the energy storage density with a charge-discharge efficiency > 90% of the polyimide high-temperature dielectric composite films in Examples 1 to 4 of the present invention gradually increase. The inventors analyzed this and believed that the reasons might be: (1) P(TFE-PPVE) has a wide bandgap (the bandgap value is 9.72 eV), which greatly inhibits the growth of electrical treeing; (2) The high carrier traps formed at the interface between P(TFE-PPVE) and PI significantly inhibit the formation of leakage current under high-temperature conditions, thereby significantly improving the high-temperature energy storage performance of the polyimide high-temperature dielectric composite film.

[0125] Under the conditions of 150 °C and a charge-discharge efficiency > 90% (exceeding 90%), the polyimide high-temperature dielectric composite film in Example 4 of the present invention exhibits an energy storage density of 3.873 J / cm 3 which shows that the polyimide high-temperature dielectric composite film provided by the present invention has excellent high-temperature energy storage performance. Compared with Comparative Examples 1 to 3, the dielectric properties and energy storage properties of the polyimide high-temperature dielectric composite films in Examples 1 to 5 of the present invention are significantly enhanced. The inventors analyzed this and believed that the reasons might be: The compatibilizing effect of fluorinated polyimide (FPI) can reduce the interfacial defects between tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (P(TFE-PPVE)) and polyimide (PI), reduce the dielectric loss of the polyimide high-temperature dielectric composite film and inhibit its leakage current under high electric field and high temperature, improve the dielectric stability of the polyimide high-temperature dielectric composite film, and enhance its dielectric properties and energy storage properties.

[0126] In summary, the polyimide high-temperature dielectric composite film prepared in the examples of the present invention has excellent dielectric properties and excellent energy storage performance in a high-temperature environment.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a polyimide high temperature dielectric composite film, characterized in that: The following steps are involved: The fluorinated polyamic acid solution is mixed with the polyamic acid solution to obtain a mixed solution, and then the mixed solution is mixed with a tetrafluoroethylene-perfluoropropyl vinyl ether copolymer solution, and then subjected to stirring treatment and ultrasonic treatment to obtain an ultrasonically treated mixed solution; The mixed solution after ultrasonic treatment is applied to the upper surface of the substrate and then dried to form an initial composite film; The initial composite film is placed in a heating device and heat-treated according to a set temperature program to obtain a heat-treated composite film, and then the heat-treated composite film is peeled off from the substrate to obtain the polyimide high-temperature dielectric composite film containing fluorinated polyimide, polyimide and tetrafluoroethylene-perfluoropropyl vinyl ether copolymer.

2. The method for preparing a polyimide high temperature dielectric composite film according to claim 1, characterized in that: In the mixed solution after ultrasonic treatment, the mass fraction of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is 10% to 30%.

3. The method for preparing a polyimide high temperature dielectric composite film according to claim 1, characterized in that: The solid content of the fluorinated polyamic acid solution is 10% to 30%, and the solid content of the polyamic acid solution is 15% to 40%.

4. The method for preparing a polyimide high temperature dielectric composite film according to claim 3, characterized in that: The mass ratio of the fluorinated polyamic acid solution to the polyamic acid solution is (0.18-0.54):2.

5.

5. The method for preparing a polyimide high temperature dielectric composite film according to claim 1, characterized in that: The set temperature program is as follows: the first stage is heating at 80℃~120℃ for 10min~20min, the second stage is heating at 180℃~220℃ for 25min~40min, the third stage is heating at 230℃~270℃ for 25min~40min, and the fourth stage is heating at 280℃~320℃ for 60min~240min.

6. The method for preparing a polyimide high temperature dielectric composite film according to claim 1, characterized in that: The drying process is carried out at a temperature of 65° C. to 100° C. and for a time of 6 hours to 24 hours.

7. The method for preparing a polyimide high temperature dielectric composite film according to claim 1, characterized in that: The stirring process has a rotation speed of 300 r / min to 1200 r / min and a time of 2 h to 8 h; And / or, the coating rate is 50s -1 ~200s -1 .

8. A polyimide high temperature dielectric composite film, characterized in that: The polyimide high temperature dielectric composite film is prepared by the preparation method of any one of claims 1 to 7.

9. The polyimide high temperature dielectric composite film according to claim 8, characterized in that: In the polyimide high temperature dielectric composite film, the highest occupied molecular orbital (HOMO) energy level of the polyimide is -5.85 eV, the lowest unoccupied molecular orbital (LUMO) energy level is -3.12 eV, and the energy band gap value is 2.73 eV.

10. The polyimide high temperature dielectric composite film according to claim 8, characterized in that: In the polyimide high temperature dielectric composite film, the highest occupied molecular orbital (HOMO) energy level of the tetrafluoroethylene-perfluoropropyl vinyl ether copolymer is -9.86 eV, the lowest unoccupied molecular orbital (LUMO) energy level is -0.14 eV, and the energy band gap value is 9.72 eV.

Citation Information

Patent Citations

  • Preparation method of highly dielectric polyimide / barium titanate composite film

    CN104046023A